Prediction Models for Descreasing Visual Acuity in Wig Makers - Ulfah, Nur; Harwanti, Siti; Ngadiman, Ngadiman (Kesmas, 2019)
One of the occupational diseases that can arise for workers with high accuracy is a decrease in their visual acuity. Therefore, it is necessary to study the risk factors of decreasing visual acuity in workers with high accuracy, such as in wig makers. This study aimed to examine the correlation between age, working period, lighting intensity, fatigue, and nutritional status with visual acuity, and to observe the main risk factors that can be used as a reference for predicting decreasing visual acuity. This study was an observational study that used a cross-sectional design. The population number for this study was 185 wig makers.A total of 85 samples were selected using simple random sampling. The study was carried out in January to March 2016 on wig makers in Purbalingga. The results showed that variables most closely associated with visual acuity were working period (p-value = 0.000 < 0.05), lighting intensity (p-value = 0.000 < 0.05), and fatigue (0.013 < 0.05). Variables that were not related to vision acuity were age (p-value = 0.846 > 0.05) and nutritional status (p-value = 0.562 > 0.05).